Rapid and Specific Detection of tdh, trh1, and trh2 mRNA of Vibrio parahaemolyticus by Transcription-Reverse Transcription Concerted Reaction with an Automated System - Nakaguchi, Yoshitsugu (American Society for Microbiology, 2004)
Vibrio parahaemolyticus strains carrying the thermostable direct hemolysin (TDH) tdh gene, the TDH-related hemolysin (trh) gene, or both genes are considered virulent strains. We previously demonstrated that the transcription-reverse transcription concerted (TRC) method could be used to quantify the amount of mRNA transcribed from the tdh gene by using an automated detection system. In this study, we devised two TRC-based assays to quantify the mRNAs transcribed from the trh1 and trh2 genes, the two representative trh genes. The TRC-based detection assays for the tdh, trh1, and trh2 transcripts could specifically and quantitatively detect 10(3) to 10(7) copies of the corresponding calibrator RNAs. We examined by the three TRC assays the total RNA preparations extracted from 103 strains of Vibrio parahaemolyticus carrying the tdh, trh1, or trh2 gene in various combinations. The tdh, trh1, and trh2 mRNAs in the total RNA preparations were specifically quantified, and the time needed for detection ranged from 9 to 19 min, from 14 to 18 min, and from 9 to 12 min, respectively. The results showed that this automated TRC assays could detect the tdh, trh1, and trh2 mRNAs specifically, quantitatively, and rapidly. The relative levels of TDH determined by the immunological method and that of tdh mRNA determined by the TRC assays for most tdh-positive strains correlated. Interestingly, the levels of TDH produced from the strains carrying both tdh and trh genes were lower than those carrying only the tdh gene, whereas the levels of mRNA did not significantly differ between the two groups.